Influência do teor residual de sulfito sobre a qualidade do camarão marinho - Gama, Lenietti Galiza (2015)
Sea shrimp’s color and texture quality may be modified due to the lack of standardization on the use of sodium metabisulfite preservative causing a higher stiffness and excessive whitening after the cooking process, making the sulfite residue content above 30 kg-1g, which is the amount allowed by the current law. The Litopenaeus vannamei shrimp samples size 80/100 were acquired in a harvesting farm on the North shore of Paraíba State and to which the metabisulfite treatment was applied (0 a 40 kg-1g) accounting for a total of eight concentrations (T1 (0), T2 (5), T3 (10), T4 (15), T5 (20), T6 (25), T7 (30) e T8 (40) kg-1g) from which their heads and shells were removed, later they were cooked in a water boiling solution (99 ± 1º C) and NaCl at 1% until the moment each sample’s core reached a temperature of 63º C and those remained boiling for 15 seconds. Following that, the samples were analyzed regarding their SO2 content in order to assess the sodium metabilsulfite’s influence over the sea shrimp’s quality while correlating the obtained values with sensory and physical analysis and considering the residual contents of the allowed sulfites. Of the eight analyzed samples, four (T1 (0), T3 (10), T5 (20) e T7 (30) kg-1g) were chosen to perform the following analysis: sensory, color, shearing force, water activity, retaining ability and cooking performance. The sensory analysis was performed with 96 untrained judges and based on the ideal scale testing methodology to assess color and texture parameters, and accepting tests to assess taste, appearance and global acceptance. The results have showed that ideal color and texture appeared on the sample treated at 20 g kg-1sodium metabisulfite, being such concentration the one recommended by the cooked shrimp manufacturer and with the same features and the correlations between sensory and physical parameters were achieved in the samples that were wetter, slightly harder and presented and a shade of orange.